A Clinical Evaluation of Kshara Karma Therapy in the Management of Cervical Erosion: A Case Report - Dr. Avni Kantharia; Prof. (Dr.) Manjusha Karkare (The Bioscan, 2026)
Introduction: Cervical erosion (cervical ectopy) is a common gynecological condition characterized by the replacement of the squamous epithelium with columnar epithelium on the ectocervix, leading to symptoms like vaginal discharge, vulval itching, and pain. Conventional biomedical treatments such as electrocautery, cryotherapy, and laser vaporization are often used, but these are invasive and carry potential side effects. This study explores the effectiveness of a holistic Ayurvedic approach for managing cervical erosion.